Sustainable graduate employability: an evaluation of 'brand me' presentations as a method for developing self-confidence. Issue 9 (1st September 2020) - Tymon, Alex; Harrison, Charlotte; Batistic, Sasa
ABSTRACT: This paper evaluates 'brand me' presentations as a method for developing employability-related self-confidence (ERSC). Measurements of ERSC were taken at three points in time from a sample of 105 full-time business and law students at a UK university. These were analysed alongside student feedback, assessment artefacts, and semi-structured interviews with students and lecturers. Findings indicate that ERSC increases over time, skills are learnt, and new behaviours are developed. We contribute to sustainable graduate employability literature by empirically demonstrating theoretically proposed links between career management learning and ERSC. Furthermore, we show that self-confidence may be a situated behaviour, rather than a fixed trait, which generates practical suggestions for career management teaching. We join the teaching excellence debate by demonstrating a method to measure learning gain in higher education. We also add to research methods knowledge by adapting an evaluation framework from the Human Resource Development field for use in this context.